Influences of Initial Position on Negotiation Approach in Solving Environmental Cases in Malaysia - Norhayati Rafida Abdul Rahim; Jusang Bolong; Ezhar Tamam; Nizam Osman (Human Resource Management Academic Research Society, 2024)
Non-Indexed Publication